Proving the Value of HR: How and Why to Measure ROI - Phillips, Jack J. (Society For Human Resource Management, 2012)
This book provides basic, step-by-step instructions to develop the ROI of HR. It is much easier to read than other ROI-based books and uses examples directly from the practice of human resources.